2022
DOI: 10.1042/bcj20210812
|View full text |Cite
|
Sign up to set email alerts
|

α-Helix stabilization by co-operative side chain charge-reinforced interactions to phosphoserine in a basic kinase-substrate motif

Abstract: How cellular functions are regulated through protein phosphorylation events that promote or inhibit protein–protein interactions (PPIs) is key to understanding regulatory molecular mechanisms. Whilst phosphorylation can orthosterically or allosterically influence protein recognition, phospho-driven changes in the conformation of recognition motifs are less well explored. We recently discovered that clathrin heavy chain recognises phosphorylated TACC3 through a helical motif that, in the unphosphorylated protei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Ac-PGEDIWKKFELLPTPPL-NH 2 (N-myc 45–61, MBI); Ac-EPPSWVTEMLLENELWG-NH 2 (N-myc 73–89, AIH); Ac-GFSAREKLERAVSEKLQ-NH 2 (N-myc 119–135, MBII+); Ac-GFSAAAKLVSEKLASYQ-NH 2 (c-myc 137–153, MBII+). Peptides were initially dissolved to give 0.5–1.0 mM stock solutions in buffer composed of 1 mM sodium borate, 1 mM sodium citrate, 1 mM (Na/H) 3 PO 4 and 10 mM NaCl, pH 7 [64, 65]. For measurements, samples were further diluted in buffer to concentrations of 10–100 μM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ac-PGEDIWKKFELLPTPPL-NH 2 (N-myc 45–61, MBI); Ac-EPPSWVTEMLLENELWG-NH 2 (N-myc 73–89, AIH); Ac-GFSAREKLERAVSEKLQ-NH 2 (N-myc 119–135, MBII+); Ac-GFSAAAKLVSEKLASYQ-NH 2 (c-myc 137–153, MBII+). Peptides were initially dissolved to give 0.5–1.0 mM stock solutions in buffer composed of 1 mM sodium borate, 1 mM sodium citrate, 1 mM (Na/H) 3 PO 4 and 10 mM NaCl, pH 7 [64, 65]. For measurements, samples were further diluted in buffer to concentrations of 10–100 μM.…”
Section: Methodsmentioning
confidence: 99%
“…Background spectra were recorded using buffer alone, buffer/15% TFE or buffer/30% TFE, and background ellipticity values were subtracted from raw sample ellipticity values ( θ ( λ )) to calculate MREs using: where M w is the peptide molecular weight, and n is the number of total peptide bonds, in each case taken to be 17 accounting for the acetyl capping group. Helicity values were estimated using the following equation: with MRE 222 in units of deg cm 2 dmol −1 res −1 [64, 66].…”
Section: Methodsmentioning
confidence: 99%
“…Batchelor et al 40 and Raza et al 41 studied the effects of pH on hydrogels. The results showed that different pH values resulted in the hydrogel formation of a-helix peptide Ac-AAQAAARQApSAAQKAY-NH 2 and the b-sheet peptide FER-8 (FEFEFRFK), respectively.…”
Section: A-helical Structurementioning
confidence: 99%
“…The effects on helix populations from phosphorylation of an IDP are typically dual. Either the helix structure is stabilized when phosphorylation occurs in N-terminus facilitated by favorable electrostatic interactions and destabilized when positioned in the C-terminus, likely due to interference with the helix dipole (Figure 2A) [55,[60][61][62]. Although the underlying structural mechanism is not clear, the presence of a phosphoryl group close to a proline can impact the relative populations of cis and trans isomers [24,63], leading to switched binding capacities and therefore function.…”
Section: Impacting the Chemistry And The Conformational Ensembles Of ...mentioning
confidence: 99%